2017
DOI: 10.1007/s11604-017-0640-0
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty of cosmetic evaluation after accelerated partial breast irradiation: interim analysis of a Japanese prospective multi-institutional feasibility study

Abstract: UMIN000001677.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…In Korea (37) and our previous report (27) regarding MIB-PBI, excellent or good cosmetic outcomes were achieved in 89.6% and 90.1%, respectively, because target volume was strictly limited, as the V 100 was 44.7 and 43.7 cm 3 , respectively. In a Japanese study involving a larger radiation volume, 70% of the patients achieved an excellent or good cosmesis, while Grade 2 or 3 breast fibrosis was observed in 26.1% of the patients (38,39). However, only Grade 2 breast fibrosis was observed in 2.5% patients in the Singaporean study also targeting a larger volume (40).…”
Section: Discussionmentioning
confidence: 93%
“…In Korea (37) and our previous report (27) regarding MIB-PBI, excellent or good cosmetic outcomes were achieved in 89.6% and 90.1%, respectively, because target volume was strictly limited, as the V 100 was 44.7 and 43.7 cm 3 , respectively. In a Japanese study involving a larger radiation volume, 70% of the patients achieved an excellent or good cosmesis, while Grade 2 or 3 breast fibrosis was observed in 26.1% of the patients (38,39). However, only Grade 2 breast fibrosis was observed in 2.5% patients in the Singaporean study also targeting a larger volume (40).…”
Section: Discussionmentioning
confidence: 93%
“…However, the complication rate was higher, with overall 16% of wound complications and 4% of rib fractures. Based on these preliminary results, we conducted the first multi-institutional prospective study in Japan using 36 Gy in six fractions [11], with a LC rate of 100% at a short-term follow-up of median 42 months [12]. At present, the longest follow-up MIB results in Japan were reported by Sato et al The authors reported on 516 MIB patients using a dose-fraction schedule of 32 Gy in eight fractions, achieving a LC rate of 97.5% with a median follow-up of 53.1 months [13].…”
Section: Purposementioning
confidence: 99%
“…83,84 Similar outcomes have been seen in smaller institutional series as well, with multilumen and strut applicators demonstrating the potential for improved toxicity profiles. [85][86][87][88][89][90] Outcomes for patients with ductal carcinoma in situ (DCIS) treated with applicator brachytherapy have been evaluated; although smaller studies suggested potentially increased rates of IBTR, the MammoSite Registry data demonstrated low rates of local recurrence in patients with DCIS. 84,91 Although traditionally delivered in 8 to 10 fractions over 4 to 5 days, shorter regimens with applicator brachytherapy have been evaluated.…”
Section: Ultrashort Partial Breast Irradiationmentioning
confidence: 99%